2014
DOI: 10.3109/09593985.2013.871764
|View full text |Cite
|
Sign up to set email alerts
|

The presentation and outcomes of shoulder pain in public hospital physiotherapy departments in NSW: an observational study

Abstract: Physiotherapy in NSW Public Health settings manages a wide variety of shoulder conditions with benefits observed across all patient presentations and diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Nonetheless, hypothetico‐deductive reasoning, intuition, and the use of clinical guidelines do not enable consistent transparent decision‐making as evidenced by the increasing numbers of imaging requests and surgery, 3,8,13 despite the apparent effectiveness of conservative rehabilitation 14‐16 . Regardless of the clinical pathway, it is recognized that clinical outcomes can be variable, and decisions are inconsistent.…”
Section: Difficulties Associated With Musculoskeletal Decision‐makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, hypothetico‐deductive reasoning, intuition, and the use of clinical guidelines do not enable consistent transparent decision‐making as evidenced by the increasing numbers of imaging requests and surgery, 3,8,13 despite the apparent effectiveness of conservative rehabilitation 14‐16 . Regardless of the clinical pathway, it is recognized that clinical outcomes can be variable, and decisions are inconsistent.…”
Section: Difficulties Associated With Musculoskeletal Decision‐makingmentioning
confidence: 99%
“…Nonetheless, hypothetico-deductive reasoning, intuition, and the use of clinical guidelines do not enable consistent transparent decision-making as evidenced by the increasing numbers of imaging requests and surgery, 3,8,13 despite the apparent effectiveness of conservative rehabilitation. [14][15][16] Regardless of the clinical pathway, it is recognized that clinical outcomes can be variable, and decisions are inconsistent. For example, a recent study found little difference between operative and non-operative treatment groups for fullthickness tears of the rotator cuff, using the quality-of-life index score.…”
Section: Difficulties Associated With Musculoskeletal Decision-makingmentioning
confidence: 99%
“…[ 7 , 15 , 16 ] Given this fact, physical therapists routinely evaluate older adults following referral from primary care providers, or by patients’ self-referral, and provide initial management for shoulder dysfunction. [ 17 , 18 ] Physical therapists typically diagnosis RC tear based on clinical examination alone, since most physical therapists do not order imaging studies for their patients. [ 19 , 20 ] Thus, in contrast to patients receiving care from orthopedic surgeons, there is a current gap in knowledge about levels of FI and progression of FI over time in the population of patients receiving initial management for RC tear by physical therapists.…”
Section: Introductionmentioning
confidence: 99%